Expression and Bioinformatics Analysis of Taurine-Upregulated Gene 1 (TUG1) in Esophageal Squamous Cell Carcinoma (ESCC) Tissue Samples Collected from Patients in Golestan Province, Northeast of Iran - Yasaman Fateri; Eisa Jorjani; Abdolvahab Moradi; Hosein Sabouri; Halime Rahimnia; Shabbou Bahramian; Zahra Roohineghad; Encieh Delshad (Golestan University Of Medical Sciences, 2020)
Background and objectives: Esophageal squamous cell carcinoma (ESCC) is the most widespread type of esophageal cancer. LncRNA TUG1 was first identified in a genomic screening study for the treatment of taurine in retinal cells. This study aimed at analyzing TUG1 expression in ESCC tissues collected from an Iranian population of patients. Bioinformatics study was also conducted for better understanding the function of this lnc-RNA. Methods: We examined the expression of TUG1 in 31 pairs of ESCC tissues and adjacent non-cancerous tissues by qRT-PCR. Bioinformatics analysis was conducted using various databases. Student's t-test was performed using SPSS software (version 16.0) to evaluate the difference in TUG1 expression between ESCC and adjacent non-cancerous tissues. Results: TUG1 expression level in ESCC tissues was significantly higher than that in the adjacent non-cancerous tissues (P=0.04). Conclusion: TUG1 is upregulated in ESCC, which may be related to history of smoking